Complexity metrics in engineering design managing the structure of design processes - Kreimeyer, Matthias (Springer, 2011)
This book presents the results of several years? research work on how to characterize complexity in engineering design with a specific regard to dependency modeling. The 52 complexity metrics that are presented show different facets of how complexity takes shape in design processes.  The metrics are supported by a modeling method and a measurement framework to employ the metrics in a goal-oriented manner.  The detailed description of all involved metrics and models makes it possible to apply the analysis approach to common process modeling methodologies.  Three case studies from automotive process management illustrate the application to facilitate the transfer to other cases in an industrial context. The comprehensive appendix supplies additional details and checklists for structural analysis to generate a complete overview of current means of structural analysis.